After effects cs5 digital classroom - Smith, Jerron (Digital classroom, 2009)
This video and full-color book combo has quite an effect for learning After Effects CS5! Adobe After Effects is a leading motion graphics and visual effects program that allows you to create and deliver compelling motion graphics and visual effects